REVIEWS - Johnstone, William (Journal of Semitic studies, 2003)
The Particulars of Rapture: Reflections on Exodus Avivah GottliebZornberg . Doubleday, New York , 2001. Pp. 582. Price: $35.00 . ISBN: 0-385-49152-2.